Preparation method and application of hyaluronic acid-based hydrogel with rapid self-healing capability and excellent mechanical property

By introducing quaternized carboxymethyl chitosan, oxidized hyaluronic acid and hydrazide hyaluronic acid into the hydrogel, co-crosslinked hydrogels are solved, and the existing hydrogels are insufficient mechanical stability, self-healing ability and antibacterial properties are achieved, and the effects of rapid self-healing, excellent mechanical properties and continuous drug release are achieved.

CN119570066APending Publication Date: 2025-03-07HENAN UNIV OF ANIMAL HUSBANDRY & ECONOMY

Patent Information

Application Number
CN202411770738.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When used as a drug sustained release carrier, existing hydrogels have poor mechanical stability and self-healing ability and insufficient antibacterial performance, resulting in limited application in the field of biomedical science.

Method used

By introducing quaternized carboxymethyl chitosan and oxidized hyaluronic acid, and adding hydrazide hyaluronic acid to the reaction system, a co-crosslinked hydrogel of imine bonds, acyl hydrazone bonds, disulfide bonds and hydrogen bonds are formed.

Benefits of technology

The hydrogel has achieved rapid self-healing, excellent mechanical properties, good antibacterial properties, sensitive pH response, biocompatibility and continuous drug release, which has enhanced its application potential in the field of biomedical science.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570066A_ABST
    Figure CN119570066A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of hyaluronic acid-based hydrogel with rapid self-healing capability and excellent mechanical performance, and can effectively solve the problems that the use efficiency is reduced or the antibacterial performance is poor due to the fact that the hyaluronic acid-based hydrogel cannot recover to the original structure and performance at the fastest speed after being damaged by external force in the prior art. In order to solve the problem that when hydrogel is in contact with a human body, local infection and inflammation can be caused, the technical scheme for solving the problem is as follows: quaternized carboxymethyl chitosan and oxidized hyaluronic acid are taken as substrate materials, hydrazide hyaluronic acid is introduced into a reaction system, and the hydrogel is prepared by virtue of a co-crosslinking effect among a dynamic imine bond, an acylhydrazone bond, a disulfide bond and a hydrogen bond. The hyaluronic acid-based hydrogel has the advantages of rapid self-healing performance, excellent mechanical performance, good pH responsiveness, biocompatibility, biodegradability, drug sustained release performance and the like, can meet the specific requirements of a drug delivery system for materials and structures, and is an innovation of the preparation method of the hyaluronic acid-based hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

1. Technical Field

[0001] The present invention relates to the field of biomedical materials, and in particular to a preparation method and application of a hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties. 2. Background Technology

[0002] Drug sustained-release technology is a key method for disease treatment in the medical field. It can reduce drug side effects, prolong drug efficacy, and improve drug bioavailability. In order to ensure stable and continuous drug release, the drug must be combined with a specific carrier to form a suitable dosage form. These carriers can sense environmental changes or respond to external stimuli, accurately deliver drugs to specific parts of the human body, and adjust the release rate, thereby achieving controlled release of drugs to achieve the effect of treating diseases. In the field of biological tissue engineering, the development of suitable drug carriers is extremely important for achieving these therapeutic goals. Hydrogel is a type of extremely hydrophilic three-dimensional polymer chain network, generally prepared by physical or chemical cross-linking. It has the advantages of simple preparation, low cost, low toxicity, and degradability. When hydrogel is used as a drug sustained-release carrier, the most important advantage is that it can be placed directly on the damaged part to avoid drug diffusion loss, thereby improving the therapeutic effect. In recent years, various types of biomass polymer materials have been widely studied as synthetic precursors for hydrogels.

[0003] At present, Chinese patent CN118415962A, named a drug controlled release system based on natural polysaccharides, preparation method and application thereof, grafts deoxy-6-arginine onto chitosan, and reacts with dialdehyde functionalized polyethylene glycol through Schiff base to prepare hydrogel as a carrier for treating diabetes drugs. Chinese patent CN109970999A, named a chitosan / polysulfonate betaine ion supply double network hydrogel and its preparation method, the hydrogel is prepared by double network cross-interpenetration, the hydrogel has good antibacterial and anti-cell adhesion properties, and shows broad application prospects in the biomedical field. Chinese patent CN109966558A, aldehyde-modified natural materials and disulfide-bonded hydrazide natural materials are reacted by Schiff base between the two to prepare injectable intelligent responsive hydrogels, the hydrogel has good injectability, biocompatibility and degradability, and is an ideal drug carrier and bioremediation material. Chinese patent CN109971042A constructs a high-strength double-network zwitterionic hydrogel, and the excellent performance of the hydrogel shows great application prospects in the biomedical field. However, hydrogels still have certain limitations when used as drug sustained-release carriers. For example, mechanical stability and self-healing ability are poor, and when damaged by external forces, they cannot be restored to the original structure and performance at the fastest speed, thereby reducing the efficiency of use. In addition, due to poor antibacterial properties, when the hydrogel comes into contact with the human body, it will also cause local infection and inflammation. These problems greatly limit the application of hydrogels in the biomedical field. Therefore, constructing a hydrogel with rapid self-healing performance and excellent mechanical properties, while having good antibacterial properties, sensitive pH responsiveness, biocompatibility, high drug loading and sustained release behavior is a technical problem that needs to be solved urgently. III. Summary of the invention

[0004] In view of the above situation, in order to solve the defects of the prior art, the purpose of the present invention is to provide a preparation method and application of a hyaluronic acid-based hydrogel with rapid self-healing ability and excellent mechanical properties, which can effectively solve the problem that the prior art cannot recover to its original structure and performance as quickly as possible after being damaged by external force, thereby reducing its use efficiency or causing local infection and inflammation when the hydrogel comes into contact with the human body due to poor antibacterial properties.

[0005] The technical solution provided by the present invention is a method for preparing the hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties, comprising the following steps:

[0006] 1) adding hyaluronic acid powder to deionized water, and continuously stirring until the hyaluronic acid is completely dissolved to form a uniform solution, then adding sodium periodate solution to the solution under light-proof conditions, allowing it to fully react for a period of time, adding ethylene glycol to the system after the reaction is completed, and continuing the reaction, after the reaction is completed, dialyzing the obtained product through a dialysis membrane to remove unreacted raw materials and by-products, thereby obtaining a pure reaction product, and finally freeze-drying the dialyzed solution to obtain oxidized hyaluronic acid powder;

[0007] 2) taking the hyaluronic acid powder prepared in step 1), adding it into PBS (phosphate buffer solution), and fully dissolving the oxidized hyaluronic acid under stirring until the solution becomes clear and transparent, thereby obtaining an oxidized hyaluronic acid solution;

[0008] 3) adding the carboxymethyl chitosan powder into deionized water and continuously stirring until it is completely dissolved, then adding trimethyl glycidyl ammonium chloride to the solution at a specific temperature, and after sufficient reaction for a period of time, dialyzing the obtained product through a dialysis membrane to remove unreacted products, and finally freeze-drying the dialyzed solution to obtain a solid powder of quaternized carboxymethyl chitosan;

[0009] 4) adding the solid powder of quaternary ammonium carboxymethyl chitosan prepared in step 3) into PBS and stirring until completely dissolved to obtain a quaternary ammonium carboxymethyl chitosan solution;

[0010] 5) dissolving 3,3'-dithiobispropionic acid methyl ester in anhydrous ethanol and stirring the mixture thoroughly, then adding hydrazine hydrate and stirring the mixture thoroughly, and then recrystallizing the solution in anhydrous ethanol to obtain a 3,3'-dithiobispropionic acid hydrazide (DTP) sample, then adding the DTP sample to a hyaluronic acid solution at room temperature and stirring the mixture thoroughly, adding carbodiimide and N-hydroxysuccinimide in sequence, and adjusting the pH value with hydrochloric acid, continuing the reaction for a period of time, and then dialyzing the reaction solution with a dialysis membrane, and finally freeze-drying the dialyzed sample to obtain a milky white hydrazide hyaluronic acid;

[0011] 6) dissolving the hydrazide hyaluronic acid prepared in step 5) in PBS phosphate buffer to obtain a hydrazide hyaluronic acid solution after complete dissolution;

[0012] 7) The oxidized hyaluronic acid solution prepared in step 2), the quaternized carboxymethyl chitosan solution prepared in step 4) and the hydrazide hyaluronic acid solution prepared in step 6) are mixed evenly to obtain a fast self-healing hyaluronic acid-based hydrogel with high mechanical properties.

[0013] In the step 1), the concentration of hyaluronic acid is 10 mg / mL, and the volume is 100 mL; the concentration of sodium periodate is 0.3-0.5 M, and the volume is 5-10 mL; the volume of ethylene glycol is 1 mL; the reaction conditions are to react at room temperature for 4-6 hours; the freeze-drying temperature and time are respectively -50°C to -40°C, and 48-60 hours.

[0014] In the step 2), the oxidized hyaluronic acid powder is dissolved in PBS phosphate buffer to obtain a 9 g / L oxidized hyaluronic acid solution.

[0015] In the step 3), the concentration of carboxymethyl chitosan is 21.8 g / L, the concentration of trimethyl glycidyl ammonium chloride is 4.5 g / L, the reaction is carried out at 55° C. for 48 hours; the sample is freeze-dried at -50° C. to -40° C. for 48-60 hours.

[0016] In the step 4), the quaternary ammonium carboxymethyl chitosan is dissolved in PBS phosphate buffer to obtain a 6 g / L quaternary ammonium carboxymethyl chitosan solution.

[0017] In the step 5), 3,3'-dithiobispropionic acid methyl ester, anhydrous ethanol and hydrazine hydrate are 1.68 mL, 45 mL and 4.5 mL respectively, the reaction temperature is 30°C, the reaction time is 12 hours, and 3,3'-dithiobispropionic acid hydrazide is obtained after recrystallization; DTP, hyaluronic acid, carbodiimide and N-hydroxysuccinimide are 1.79 g, 100 mL, 0.47 g and 0.29 g respectively, the reaction temperature is 25°C, and the reaction time is 12-24 hours; the freeze-drying temperature and time are -50°C to -40°C, 48-60 hours respectively.

[0018] In the step 6), hydrazide hyaluronic acid is dissolved in PBS phosphate buffer to obtain 1.5 g / L hydrazide hyaluronic acid.

[0019] In the step 7), the volume ratio of the quaternized carboxymethyl chitosan solution, the oxidized hyaluronic acid solution and the hydrazide hyaluronic acid is 1:2:2; and the reaction temperature is 25-37°C.

[0020] The invention discloses an application of the hyaluronic acid-based hydrogel with rapid self-healing ability and excellent mechanical properties in a drug delivery system.

[0021] The present invention uses quaternized carboxymethyl chitosan and oxidized hyaluronic acid as base materials, introduces hydrazide hyaluronic acid into the reaction system, and prepares the hydrogel by co-crosslinking between dynamic imine bonds, acylhydrazone bonds, disulfide bonds and hydrogen bonds. The hydrogel has the advantages of rapid self-healing performance, excellent mechanical properties, good pH responsiveness, biocompatibility, biodegradability and sustained drug release performance, etc., and can meet the specific requirements of the drug delivery system for materials and structures. It is an innovation in the preparation method of hyaluronic acid-based hydrogel. IV. Description of the drawings

[0022] Figure 1 The structural principle diagram of the hydrogel prepared by the present invention.

[0023] Figure 2 This is a physical picture of the hydrogel obtained in Example 7 of the present invention.

[0024] Figure 3 This is a physical picture of the rapid self-healing of the hydrogel obtained in Example 7 of the present invention.

[0025] Figure 4 This is a physical picture showing the excellent mechanical properties of the hydrogel obtained in Example 7 of the present invention.

[0026] Figure 5 The following are SEM images of the hydrogels obtained in Examples 1-7 of the present invention.

[0027] Figure 6 Graphs showing drug release after drug loading in hydrogels obtained in Examples 1-7 of the present invention, wherein 6a is pH=4, 6b is pH=7.4, and 6c is pH=10.

[0028] Figure 7 Graph showing the cell compatibility of the hydrogels obtained from the control group of the present invention and Examples 1-7 of the present invention.

[0029] Figure 8 Graph showing the antibacterial properties of the hydrogels obtained in Examples 1-7 of the present invention. V. Specific implementation methods

[0030] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples.

[0031] Example 1

[0032] The present invention, when implemented, specifically comprises the following steps:

[0033] 1) Dissolve hyaluronic acid in 100 mL of deionized water to obtain a hyaluronic acid solution with a concentration of 10 mg / mL, stir well and add 5 mL of 0.3 M sodium periodate solution, react at 25° C. in the dark for 6 h, then add 1 mL of ethylene glycol to terminate the reaction, and continue stirring for 1 h. After the reaction is completed, the product is dialyzed with deionized water for purification for 2-4 days, during which the dialysis water needs to be replaced 2-5 times a day. Finally, the dialyzed solution is freeze-dried in a -50° C. freeze dryer for 48 h to obtain oxidized hyaluronic acid powder;

[0034] The chemical structure of oxidized hyaluronic acid is shown below:

[0035]

[0036] 2) dissolving 0.09 g of the oxidized hyaluronic acid obtained in step 1) in 1 mL of PBS phosphate buffer, and after complete dissolution, the concentration of the oxidized hyaluronic acid solution obtained was 9% (w / v);

[0037] 3) dissolving carboxymethyl chitosan in 100 mL of deionized water to obtain a carboxymethyl chitosan solution with a concentration of 21.8 g / L, then adding methyl glycidyl ammonium chloride with a concentration of 4.5 g / L to the solution, and maintaining the reaction at 55° C. for 48 hours. After the reaction is completed, the product is dialyzed and purified with deionized water for 2-4 days, and the dialysis water is replaced 2-5 times a day. Finally, the dialyzed solution is freeze-dried in a -50° C. freeze dryer for 48 hours to obtain a solid powder of quaternized carboxymethyl chitosan;

[0038] The chemical structure of quaternized carboxymethyl chitosan is shown below:

[0039]

[0040] 4) dissolving 0.06 g of the quaternized carboxymethyl chitosan prepared in step 3) in 1 mL of PBS phosphate buffer until the concentration of the quaternized carboxymethyl chitosan solution is 6% (w / v) after complete dissolution;

[0041] 5) 1.68 mL of 3,3'-dithio(bis)propionic acid methyl ester was dissolved in 45 mL of anhydrous ethanol, and 4.5 mL of hydrazine hydrate was added and stirred sufficiently. The reaction temperature was 30° C. and the reaction time was 12 h. The solution was recrystallized in anhydrous ethanol to obtain a 3,3'-dithiobispropionic acid hydrazide (DTP) sample. Subsequently, 1.79 g of the DTP sample was added to 100 mL of a 1% hyaluronic acid solution at room temperature and stirred sufficiently. 0.47 g of carbodiimide and 0.29 g of N-hydroxysuccinimide were added in sequence, and the pH was adjusted to 4-5 with 1 M hydrochloric acid. The reaction temperature was 25° C. and the reaction time was 12 h. The reaction solution was dialyzed with deionized water for 2-4 days, and the dialysis water was replaced 2-5 times a day. Finally, the dialyzed solution was freeze-dried in a -50° C. freeze dryer for 48 h to obtain a milky white hydrazide hyaluronic acid.

[0042] The chemical structure of hydrazide hyaluronic acid is shown below:

[0043]

[0044] 6) dissolving 0.015 g of the hydrazide hyaluronic acid prepared in step 5) in 1 mL of PBS phosphate buffer until the concentration of the hydrazide hyaluronic acid is 1.5% (w / v) after complete dissolution;

[0045] 7) The oxidized hyaluronic acid solution prepared in step 2), the quaternized carboxymethyl chitosan solution prepared in step 4), and the hydrazide hyaluronic acid solution prepared in step 6) are fully mixed at a volume ratio of 1:2:2 at 37° C., and then cooled and molded at room temperature to obtain a hyaluronic acid-based hydrogel with rapid self-healing and high mechanical properties.

[0046] The present invention uses quaternized carboxymethyl chitosan (QCS) and oxidized hyaluronic acid (AHA) as raw materials, and introduces hydrazide hyaluronic acid (DHA) into the reaction system to develop a double cross-linked hydrogel with rapid self-healing ability and excellent mechanical properties. The hydrogel is prepared by imine bonds, acylhydrazone bonds, disulfide bonds and hydrogen bonds formed between QCS, AHA and DHA. The introduction of DHA introduces disulfide bonds and more amino, hydroxyl and other functional groups into the reaction system, increases the active sites of cross-linking inside the hydrogel, further improves the cross-linking degree of the hydrogel, and thus makes it have more excellent performance. The dynamic reversibility of imine bonds, acylhydrazone bonds and disulfide bonds improves the self-healing ability and wide pH responsiveness of the hydrogel, and their strong interaction with hydrogen bonds has a stabilizing effect on the structure of the hydrogel. In addition, acetylsalicylic acid (ASA) was used as a model drug to detect its sustained-release behavior in the hydrogel. The morphology, mechanical properties, self-healing properties, thermal stability and pH responsiveness of the hydrogel were investigated by thermogravimetric analysis, infrared spectroscopy and field emission scanning electron microscopy, and its feasibility as a drug sustained-release carrier was explored. The relevant experimental data are as follows:

[0047] like Figure 1 As shown in the figure, quaternized carboxymethyl chitosan and oxidized hyaluronic acid were used as the base materials, hydrazide hyaluronic acid was introduced into the reaction system, and the double cross-linked hydrogel with rapid self-healing ability and higher mechanical properties was prepared by forming interactions between imine bonds, acylhydrazone bonds, disulfide bonds and hydrogen bonds. In the hydrogel system, the addition of hydrazide hyaluronic acid can introduce disulfide bonds and more active functional groups such as amino groups and hydroxyls into the reaction system, promote the cross-linking of imine bonds, acylhydrazone bonds and more hydrogen bonds, and establish a dynamic network through the reversible interaction between the cross-linked bonds, so that the hydrogel has rapid self-healing ability and higher mechanical properties. In addition, the dynamic reversibility of disulfide bonds improves the self-healing efficiency of the hydrogel and its ability to adapt to a wide range of pH. Under the interaction of multiple dynamic covalent bonds and hydrogen bonds, the hydrogel has stable mechanical properties. Due to the presence of quaternary amine groups, the hydrogel has significant antibacterial properties. In addition, the hydrogel can be self-degraded without obvious biological toxicity, and acetylsalicylic acid is used as the target drug to explore its sustained release behavior in the hydrogel.

[0048] Example 1

[0049] 1) Dissolve hyaluronic acid in 100 mL of deionized water to obtain a hyaluronic acid solution with a concentration of 10 mg / mL, stir well and add 5-10 mL of a 0.3-0.5 M sodium periodate solution, react at 25° C. in the dark for 4-10 hours, add ethylene glycol after the reaction to terminate the reaction, and continue stirring for 1 hour. After the reaction, dialyze the product with deionized water for purification for 2-4 days, during which the dialysis water needs to be replaced 2-5 times a day, and finally freeze-dry the dialyzed solution in a freeze dryer at 50° C. to -40° C. for 48-60 hours to obtain oxidized hyaluronic acid;

[0050] 2) dissolving 0.09 g of the oxidized hyaluronic acid obtained in step 1) in 1 mL of PBS phosphate buffer, and after complete dissolution, the concentration of the oxidized hyaluronic acid solution obtained was 9% (w / v);

[0051] 3) dissolving carboxymethyl chitosan in 100 mL of deionized water to obtain a carboxymethyl chitosan solution with a concentration of 21.8 g / L, then adding methyl glycidyl ammonium chloride with a concentration of 4.5 g / L to the solution, and maintaining the reaction at 55° C. for 48 hours. After the reaction is completed, the product is dialyzed and purified with deionized water for 2-4 days, and the dialysis water is replaced 2-5 times a day. Finally, the dialyzed solution is freeze-dried in a freeze dryer at 50° C. to -40° C. for 48-60 hours to obtain quaternized carboxymethyl chitosan;

[0052] 4) dissolving 0.06 g of the quaternary ammonium carboxymethyl chitosan obtained in step 3) in 1 mL of PBS phosphate buffer until the concentration of the quaternary ammonium carboxymethyl chitosan solution is 6% (w / v) after complete dissolution;

[0053] 5) The solution prepared in step 2) was added to the solution prepared in step 4) at a mixing volume ratio of 1:2. After sufficient reaction at 37° C., the mixture was transferred to a mold to obtain a hyaluronic acid-based hydrogel QCS+AHA.

[0054] Example 2

[0055] 1) Dissolve hyaluronic acid in 100 mL of deionized water to obtain a hyaluronic acid solution with a concentration of 10 mg / mL. After fully stirring, add 5-10 mL of sodium periodate solution with a concentration of 0.3-0.5 M. React at 25°C in the dark for 4-10 hours. After the reaction, add ethylene glycol to terminate the reaction and continue stirring for 1 hour. After the reaction, the product is dialyzed with deionized water for purification for 2-4 days, during which the dialysis water needs to be replaced 2-5 times a day. Finally, the dialyzed solution is freeze-dried in a freeze dryer at 50°C to -40°C for 48-60 hours to obtain oxidized hyaluronic acid;

[0056] 2) dissolving 0.09 g of the oxidized hyaluronic acid obtained in step 1) in 1 mL of PBS phosphate buffer, and after complete dissolution, the concentration of the oxidized hyaluronic acid solution obtained was 9% (w / v);

[0057] 3) Take 3,3'-dithio (di) propionic acid methyl ester and dissolve it in anhydrous ethanol, add a certain amount of hydrazine hydrate and stir it thoroughly. After that, the solution is recrystallized in anhydrous ethanol to obtain a 3,3'-dithio dipropionyl hydrazide (DTP) sample. Subsequently, a certain amount of DTP sample is added to a hyaluronic acid solution with a concentration of 1% at room temperature and stirred thoroughly. Carbodiimide and N-hydroxysuccinimide are added in sequence, and the pH is adjusted to 4-5 with 1M hydrochloric acid. The reaction is continued for 12-24 hours, and the reaction solution is dialyzed with deionized water. The dialysis time lasts for 2-4 days, and the dialysis water is replaced 2-5 times a day. Finally, the dialyzed solution is freeze-dried in a freeze dryer at 50°C to -40°C for 48-60 hours to obtain a milky white hydrazide hyaluronic acid;

[0058] 4) dissolving 0.015 g of the hydrazide hyaluronic acid obtained in step 3) in 1 mL of PBS phosphate buffer until the concentration of the hydrazide hyaluronic acid is 1.5% (w / v) after complete dissolution;

[0059] 5) adding the solution prepared in step 2) to the solution obtained in step 4) at a mixing volume ratio of 1:2, and transferring to a mold after sufficient reaction at 37° C. to obtain a hyaluronic acid-based hydrogel OHA+DHA.

[0060] Example 3

[0061] The present invention provides a method for preparing a hyaluronic acid-based hydrogel with rapid self-healing and high mechanical properties, comprising the following steps:

[0062] 1) Dissolve hyaluronic acid in 100 mL of deionized water to obtain a hyaluronic acid solution with a concentration of 10 mg / mL. After fully stirring, add 5-10 mL of sodium periodate solution with a concentration of 0.3-0.5 M. React at 25°C in the dark for 4-10 hours. After the reaction, add ethylene glycol to terminate the reaction and continue stirring for 1 hour. After the reaction, the product is dialyzed with deionized water for purification for 2-4 days, during which the dialysis water needs to be replaced 2-5 times a day. Finally, the dialyzed solution is freeze-dried in a freeze dryer at 50°C to -40°C for 48-60 hours to obtain oxidized hyaluronic acid;

[0063] 2) dissolving 0.09 g of the oxidized hyaluronic acid obtained in step 1) in 1 mL of PBS phosphate buffer, and after complete dissolution, the concentration of the oxidized hyaluronic acid solution obtained was 9% (w / v);

[0064] 3) Take carboxymethyl chitosan and dissolve it in 100 mL of deionized water to obtain a carboxymethyl chitosan solution with a concentration of 21.8 g / L, then add methyl glycidyl ammonium chloride with a concentration of 4.5 g / L to the solution, and maintain the reaction at 55°C for 48 hours. After the reaction is completed, the product is dialyzed and purified with deionized water for 2-4 days, and the dialysis water is replaced 2-5 times a day. Finally, the dialyzed solution is freeze-dried in a freeze dryer at 50°C to -40°C for 48-60 hours to obtain quaternized carboxymethyl chitosan;

[0065] 4) dissolving 0.06 g of the quaternized carboxymethyl chitosan obtained in step 3) in 1 mL of PBS phosphate buffer, and obtaining a quaternized carboxymethyl chitosan solution with a concentration of 6% (w / v) after complete dissolution;

[0066] 5) Take 3,3'-dithio (di) propionic acid methyl ester and dissolve it in anhydrous ethanol, add a certain amount of hydrazine hydrate and stir it thoroughly. After that, the solution is recrystallized in anhydrous ethanol to obtain a 3,3'-dithio dipropionyl hydrazide (DTP) sample. Subsequently, a certain amount of DTP sample is added to a hyaluronic acid solution with a concentration of 1% at room temperature, and stirred thoroughly, and carbodiimide and N-hydroxysuccinimide are added in sequence, and the pH is adjusted to 4-5 with 1M hydrochloric acid, and the reaction is continued for 12-24 hours. The reaction solution is dialyzed with deionized water for 2-4 days, and the dialysis water is replaced 2-5 times a day. Finally, the dialyzed solution is freeze-dried in a freeze dryer at 50°C to -40°C, and the time is controlled at 48-60 hours to obtain a milky white hydrazide hyaluronic acid;

[0067] 6) dissolving 0.015 g of the hydrazide hyaluronic acid obtained in step 5 in 1 mL of PBS phosphate buffer until the concentration of the hydrazide hyaluronic acid is 1.5% (w / v) after complete dissolution;

[0068] 7) The oxidized hyaluronic acid solution obtained in step 2), the quaternized carboxymethyl chitosan solution obtained in step 4) and the hydrazide hyaluronic acid solution obtained in step 6) are mixed at a volume ratio of 1:2:2 at 25-37° C. and then cooled at room temperature to obtain a hyaluronic acid-based hydrogel QCS+OHA+DHA.

[0069] from Figure 2 The actual picture of the hydrogel shows that the hydrogel has a complete structure. Figure 3This is a real picture of the self-healing of the hydrogel. It can be seen from the figure that after the original long strip of hydrogel is cut into several sections and put together again, after 10 minutes of contact with each other without external interference, the QCS+OHA+DHA hydrogel can quickly self-heal together, and after stretching the two ends, there is no cracking on the cut surface, indicating that the hydrogel has good self-healing properties.

[0070] Figure 4 The compression test is a stress-compression strain curve measured by a universal testing machine at a sensor of 3000N and a rate of 2mm / min. Example 1, Example 2, and Example 3 represent the hydrogels obtained under the conditions of QCS+OHA, OHA+DHA, and QCS+OHA+DHA, respectively. Figure 4 It can be seen that the stress-compression strain of the hydrogel obtained under the conditions of QCS+OHA+DHA is the highest, indicating that the interaction between imine bonds, acylhydrazone bonds, disulfide bonds and hydrogen bonds can improve the mechanical stability of the hydrogel.

[0071] Figure 5 The scanning electron microscope image of the hydrogel is shown, from which it can be observed that the hydrogel has a uniformly distributed porous structure. This structural feature gives the hydrogel a large drug loading capacity and sustained drug release performance.

[0072] Figure 6 Parts a, b, and c show that the hydrogels prepared according to Examples 1 to 3 exhibit sustained drug release characteristics under pH values ​​of 4, 7.4, and 10, respectively. Since the hydrolysis rates of imine bonds and acylhydrazone bonds are faster in an acidic environment, the drug release rate is fastest in an environment with a pH value of 4, while in environments with pH values ​​of 7.4 and 10, the drug release rate is relatively slow.

[0073] Figure 7 The proliferation of mouse fibroblasts (L929) was detected by MTT direct contact method. The results showed that during the cell culture process of 1 day, 3 days and 5 days, there was no significant difference in cell viability between the experimental group adding the hydrogel of the present invention and the control group without the hydrogel. This result shows that the hydrogel has excellent biocompatibility.

[0074] Figure 8 The antibacterial performance of the hydrogels was tested against Escherichia coli and Staphylococcus aureus using the punching method. The results showed that a clear antibacterial ring was formed around the hydrogels, which confirmed that the hydrogels had excellent antibacterial activity.

[0075] The present invention introduces hydrazide hyaluronic acid (DHA) into the reaction system of quaternized chitosan (QCS) and oxidized hyaluronic acid (OHA), adopts a "one-pot" reaction strategy, and can construct a hydrogel by forming multiple strong interactions such as disulfide bonds, imine bonds, acylhydrazone bonds and hydrogen bonds without adding any toxic cross-linking agents. The resulting hydrogel exhibits excellent and rapid self-healing ability, can restore 97% of its structural integrity within 10 minutes, and has a compressive stress of up to 597KPa. In addition, the hydrogel has a sensitive response to changes in pH and can achieve sustained release of drugs. At the same time, it also exhibits excellent cell compatibility and antibacterial properties. In summary, the hydrogel has great application potential in the biomedical field, especially in the fields of drug delivery systems and tissue engineering.

[0076] It should be pointed out that the above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession can make changes or modify the technical contents disclosed above into equivalent embodiments with equivalent changes without departing from the scope of the technical solution of the present invention, which all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hyaluronic acid-based hydrogel with rapid self-healing ability and excellent mechanical properties, characterized in that: The following steps are involved: 1) Adding hyaluronic acid powder to deionized water and continuously stirring until the hyaluronic acid is completely dissolved to form a uniform solution, then adding sodium periodate solution to the solution under light-proof conditions, allowing it to fully react for a period of time, adding ethylene glycol to the system after the reaction is completed, and continuing the reaction, after the reaction is completed, dialyzing the obtained product through a dialysis membrane to remove unreacted raw materials and by-products, thereby obtaining a pure reaction product, and finally freeze-drying the dialyzed solution to obtain oxidized hyaluronic acid powder; 2) taking the hyaluronic acid powder prepared in step 1), adding it into PBS, and fully dissolving the oxidized hyaluronic acid under stirring until the solution becomes clear and transparent, thereby obtaining an oxidized hyaluronic acid solution; 3) adding carboxymethyl chitosan powder into deionized water and continuously stirring until completely dissolved, then adding trimethyl glycidyl ammonium chloride to the solution at a specific temperature, and after sufficient reaction for a period of time, dialyzing the obtained product through a dialysis membrane to remove unreacted products, and finally freeze-drying the dialyzed solution to obtain a solid powder of quaternized carboxymethyl chitosan; 4) adding the solid powder of quaternary ammonium carboxymethyl chitosan prepared in step 3) into PBS and stirring until completely dissolved to obtain a quaternary ammonium carboxymethyl chitosan solution; 5) Dissolve 3,3'-dithiobispropionic acid methyl ester in anhydrous ethanol and stir well, then add hydrazine hydrate and stir well, then recrystallize the solution in anhydrous ethanol to obtain a 3,3'-dithiobispropionic acid hydrazide sample, then add the DTP sample to the hyaluronic acid solution at room temperature and stir well, add carbodiimide and N-hydroxysuccinimide in sequence, and adjust the pH with hydrochloric acid, continue to react for a period of time, dialyze the reaction solution with a dialysis membrane, and finally, freeze-dry the dialyzed sample to obtain a milky white hydrazide hyaluronic acid; 6) dissolving the hydrazide hyaluronic acid prepared in step 5) in PBS phosphate buffer to obtain a hydrazide hyaluronic acid solution after complete dissolution; 7) The oxidized hyaluronic acid solution prepared in step 2), the quaternized carboxymethyl chitosan solution prepared in step 4) and the hydrazide hyaluronic acid solution prepared in step 6) are mixed evenly to obtain a fast self-healing hyaluronic acid-based hydrogel with high mechanical properties.

2. The method for preparing a hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties according to claim 1, characterized in that: In the step 1), the concentration of hyaluronic acid is 10 mg / mL, and the volume is 100 mL; the concentration of sodium periodate is 0.3-0.5 M, and the volume is 5-10 mL; the volume of ethylene glycol is 1 mL; the reaction conditions are to react at room temperature for 4-6 hours; the freeze-drying temperature and time are -50°C to -40°C, and 48-60 hours, respectively.

3. The method for preparing a hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties according to claim 1, characterized in that: In the step 2), the oxidized hyaluronic acid powder is dissolved in PBS phosphate buffer to obtain a 9 g / L oxidized hyaluronic acid solution.

4. The method for preparing a hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties according to claim 1, characterized in that: In the step 3), the concentration of carboxymethyl chitosan is 21.8 g / L, the concentration of trimethyl glycidyl ammonium chloride is 4.5 g / L, the reaction is carried out at 55°C for 48 hours; the sample is freeze-dried at -50°C to -40°C for 48-60 hours.

5. The method for preparing a hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties according to claim 1, characterized in that: In the step 4), the quaternary ammonium carboxymethyl chitosan is dissolved in PBS phosphate buffer to obtain a 6 g / L quaternary ammonium carboxymethyl chitosan solution.

6. The method for preparing a hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties according to claim 1, characterized in that: In the step 5), 3,3'-dithiobispropionic acid methyl ester, anhydrous ethanol and hydrazine hydrate are 1.68 mL, 45 mL and 4.5 mL respectively, the reaction temperature is 30°C, the reaction time is 12 h, and 3,3'-dithiobispropionic acid hydrazide is obtained after recrystallization; DTP, hyaluronic acid, carbodiimide and N-hydroxysuccinimide are 1.79 g, 100 mL, 0.47 g and 0.29 g respectively, the reaction temperature is 25°C, and the reaction time is 12-24 h; the freeze-drying temperature and time are -50°C to -40°C, 48-60 h respectively.

7. The method for preparing a hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties according to claim 1, characterized in that: In the step 6), hydrazide hyaluronic acid is dissolved in PBS phosphate buffer to obtain 1.5 g / L hydrazide hyaluronic acid.

8. The method for preparing a hyaluronic acid-based hydrogel having rapid self-healing ability and excellent mechanical properties according to claim 1, characterized in that: In the step 7), the volume ratio of the quaternized carboxymethyl chitosan solution, the oxidized hyaluronic acid solution and the hydrazide hyaluronic acid is 1:2:2; and the reaction temperature is 25-37°C.

9. Use of the hyaluronic acid-based hydrogel with rapid self-healing ability and excellent mechanical properties prepared by the method according to any one of claims 1 to 8 in a drug delivery system.

Citation Information

Patent Citations

  • Injectable intelligent response hydrogel and preparation method and application thereof

    CN109966558A

  • Chitosan / polysulphobetaine ionic and covalent double-network hydrogel and production method thereof

    CN109970999A

  • High-strength double-network zwitter-ion hydrogel and production method thereof

    CN109971042A

  • Drug controlled release system based on natural polysaccharide, preparation method and application thereof

    CN118415962A

Cited By

  • Antibacterial hydrogel with wet surface adhesion

    CN120098289A